Shape, membrane morphology, and morphodynamic response of metabolically active human mitochondria revealed by scanning ion conductance microscopy - Eric Lieberwirth; Anja Schaeper; Regina Lange; Ingo Barke; Simone Baltrusch; Sylvia Speller (Beilstein Journal of Nanotechnology)
Mitochondrial network dynamics play a key role in enabling cells to adapt to environmental changes. Fusion and fission of mitochondria, as well as their contact with other organelles, are central processes. Consequently, the outer membrane, which separates the mitochondrion from the cytoplasm, has become a focus of investigation. We analysed metabolically active mitochondria from HeLa cells using scanning ion conductance microscopy to generate nanoscopically resolved, three-dimensional topographies. Our measurements reveal the diversity of mitochondrial shapes. Moreover, a morphodynamic effect was identified, the magnitude of which depends on mitochondrial viability. This method, applied for the first time to mitochondria, shows potential for visualising the morphodynamic responses of mitochondria to their local environment. The similarities between the nanopipette in the measurement setup and the microtubules in the cellular context are discussed as the basis for the hypothesis.